1001 buildings you must see before you die - Irving, Mark.; StJohn, Peter, 1959- (New York : Universe, 2007)
A guide to the world's greatest architectural achievements presents concise information about each featured structure, including who designed it, who commissioned it, key dates in its construction, and descriptions of the interior and exterior.
Includes indexes.
'A Quintessence book.'
Keywords: Architecture; Buildings -- Guidebooks; Architecture -- History; Engineering -- History